Structure and phase composition of tungsten alloys modified by compression plasma flows and high-intense pulsed ion beam impacts; Applied Surface Science; Vol. 491 - Shimanskii V. I. Vitali Igorevich; Uglov V. V. Vladimir Vasilievich; Cherenda N. N. Nikolay Nikolaevich; Pigasova V. S.; Astashinsky V. M. Valentin Mironovich; Kuzmitsky A. M. Anton Mikhaylovich; Zhong H. W. Haowen; Zhang S. J.; Le X. Y. Xiaoyun; Remnev G. E. Gennady Efimovich (2019, 2019)
Title screen